Fertility Status of Pangean Reservoir Pangean District Kuantan Singingi Regency Based on Phytoplankton - Miranda Wahyuni Raja Gukguk; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPhythoplankton is a parameter used to determine the fertility status of a waters. A research aim to determine types and abundance of phytoplankton in the Pangean Reservoir has been carried out on June-July 2019. There were four sampling sites, namely S1 is in the upstream (a little floating net cage), S2 (lots of floating net cage), S3 (around rubber plantations), S4 (outlet and closest to the DAM). Water sampler were taken once/week for 3 week period. Water quality parameters measured were temperature, brightness, depth, pH, dissolved oxygen, free CO2, nitrate and phosphate.Results shown that there are 48 species of phytoplankton present in the swamp.They were classified into six classes, namely: Cyanophyceae (10 species), Bacillariophyceae (12 species),Euglenophyceae (4 species), Chloropyhceae (18 species), Xanthophyceae (3 species) and Trebouxiophyceae (1 species). The average of phytoplankton abundance was around 560.267 –1.560.785 cells/L. The water quality parameters were as follows : temperatures 29-31 0C, brightness 93-102 cm, depth 248-388 cm ,pH 5, Dissolved Oxygen 5,13-7,17 mg/L, free CO2 19-35 mg/L , nitrate 0,027-0,065 mg/L and phosphate 0,029-0,054 mg/L. Based on the Phythoplankton value, the Pangean reservoir can be categorized as high (eutrophic).Keywords :Phythoplankton, Water quality parameters, Eutrophic